Understanding Behavioral Drivers Behind Students Intentions to Limit Ultra-Processed Food Intake - Fairuz Alifah; Abdul Wahib Muhaimin; Tri Wahyu Nugroho (Postgraduate, University of Mataram, 2025)
Indonesia faces increasing public health challenges due to the rising consumption of ultra-processed foods (UPF) driven by industrialization and urbanization. This study aims to identify the behavioral determinants influencing students’ intentions to reduce UPF consumption by extending the Theory of Planned Behavior (TPB) with health consciousness and environmental concern. A quantitative explanatory design was applied involving 936 students in Malang City selected through purposive sampling. Data were collected using a structured online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 7.0. The results show that attitude, perceived behavioral control, and environmental concern significantly and positively affect students’ intentions to reduce UPF consumption (p < 0.01). Both health consciousness and environmental concern act as significant mediators linking attitude, subjective norms, and perceived behavioral control with behavioral intention. The model explains 48.5% of the variance in students’ behavioral intentions (R² = 0.485), indicating moderate predictive power. These findings emphasize the role of health and environmental awareness in shaping healthy and sustainable dietary intentions among university students. The study suggests that health and science education programs integrating behavioral and sustainability perspectives can effectively encourage reduced UPF consumption.